Simultaneous Determination of Columbianadin and Its Metabolite Columbianetin in Rat Plasma by LC-MS/MS: Application to Pharmacokinetics of Columbianadin after Oral Administration. (19th September 2018) - Li, Jin; Li, Zhen; Luo, Qian; Wang, Chun-Peng; He, Jun; Pang, Xiaoli; Teye Azietaku, John; Chang, Yan-xu
Abstract : Columbianadin and its metabolite columbianetin exhibited the anti-inflammatory, analgesic, calcium channel blocking and antitumor activities. To compare the differences between pharmacokinetics of columbianadin and its metabolite columbianetin after oral administration of pure columbianadin and Angelicae Pubescentis Radix (APR) extract, a simple and sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was established and validated to simultaneously determine columbianadin and columbianetin in rat plasma. Two analytes and an internal standard (warfarin) were well separated and determined after liquid-liquid extraction with ethyl acetate. Ammonium acetate aqueous solution (1 mmol/L) and acetonitrile were used as the mobile phase and the flow rate was 0.3 mL/min. The lower limit of quantification (LLOQ) was 0.1 ng/mL for columbianetin and 0.5 ng/mL for columbianadin, respectively. There were significant differences between some pharmacokinetic parameters and bioavailability of columbianadin after oral administration of pure columbianadin and APR extract. The studies on comparative pharmacokinetics of columbianadin were of great use for facilitating the clinical application of columbianadin and were also highly meaningful for the potential development of APR.